Glazing design for bilateral daylighting in public school classrooms in northern part of Algeria - Abdelhakim, Mesloub (2015)
Daylight quality and quantity in Algerian schools display a serious condition in ensuring the visual comfort of students and teachers. Some problems arise due to poor window design and excessive amounts of daylight penetration into the classrooms as well as non-uniform daylight distribution, which may cause glare and heat gain. This study aimed at choosing an ideal window size and glazing pattern to maximise daylight effectiveness and occupant comfort in Algerian schools. Field measurements of selected classrooms were carried out in selected schools in Algeria during the summer and winter seasons. The data were analysed and used to develop a model design for simulation. Seven patterns of glazing window design was used for an extensive simulation exercise. The results of the investigation from the site measurements show that WWR was more than 40%; the WPI was found to be within the range of 300lux to 500lux and the DF of 4%, which exceeded reference value, except the southeast orientation which recorded 2.98%. Results from the simulation using IES <VE> by comparing three different glazing types (tint, clear and reflective) and using different glazing size from 25% to 75% in winter (under overcast sky condition) and summer (under intermediate sky condition). The evidence from this study suggests that tinted windows in both winter and summer is ideal as the simulation’s result shows that significant usable area (31.22% - 41.74%) is achievable in a bilateral window opening with a DF<2 by increasing the percentage of the tinted glass from 25% to 75%. From the results this research suggests that a 30% WWR with a tinted glass of 50% VT in a bilateral school design would be ideal for public schools in Algeria as it yielded a WPI within the range of 300lux to 500lux. The use of different glazing configurations during the experiment had a significant impact in the improvement of the quantity and quality of daylighting.